Implementasi Komunikasi Pelaksanaan Program BUMDES di Desa Pantae Kecamatan Biboki Selatan Kabupaten Timor Tengah Utara - Margreth Ziska Gah; Aloysius Liliwery; Ajiz Salim Adang Djaha (Jurnal EBI, 2021)
The purpose of this study was to determine and analyze the communication process in the implementation of the BUMDes program in Pantae Village. This research is a type of qualitative research using Organizational Communication Theory in a policy implementation approach, which looks at the communication process within the organization, namely internal communication as well as external communication. Data collection techniques using observation, interviews, and document study. Data analysis used Miles and Huberman's model. The results obtained are that the internal communication process seen from vertical communication is still not running well, instructions for tasks and work from the head of BUMDes to BUMDes executives are not carried out and communication in terms of reporting and accountability is not carried out properly. Horizontal communication in the implementation of the BUMDes program has been carried out well, the process of delivering messages is carried out well, but there are obstacles in the form of frequency for communicating which are still lacking. In the context of external communication carried out by BUMDes, it was found that the communication process between BUMDes and the Inspectorate of TTU Regency had been carried out properly and in the form of formal communication, the obstacle encountered was the inability of BUMDes officials in compiling financial accountability reports which resulted in obstruction of the communication process. While the results of research related to BUMDes communication with the community, it was found that the communication process was not carried out properly. The low level of community participation is caused by the fact that the communication that is built is not participative communication.